New Opportunities of Phasegraphy in Medical Practice - Fainzilberg, L.S. (Science and Innovation, 2024)
The results of the modernization of phasegraphy (an innovative method of electrocardiogram processing) have been presented. New software and hardware which expand the method capacity have been described. The results of tests on clinical facilities of medical partner has been showed.